2014
DOI: 10.3892/or.2014.3327
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate-1 and Golgi phosphoprotein 3 are downstream targets of miR-126 in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common histologic subtype in China. It has been suggested that abnormal expression of microRNAs (miRNAs) is associated with carcinogenesis. We investigated miR-126 expression and its potential targets in ESCC. The expression of miR-126 was detected in cancerous and paired paracancer tissues from 102 patients with ESCC. Target analysis of miR-126 was predicted using online tools. The effect of miR-126 expression on target proteins was assessed using miR-126 mimics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…miRNAs promote mRNA degradation by inhibiting translation upon binding to the 3'-untranslated region (3'-UTR) of their target mRNA (12). Complementary binding of an miRNA and mRNA is not exclusive; a single miRNA can target hundreds of mRNAs, which was demonstrated in the present study and a single mRNA can be affected by multiple miRNAs (13)(14)(15)(16)(17). Consequently, miRNAs can act as tumor suppressors or possibly oncogenes depending on the target mRNAs (18,19).…”
Section: Introductionmentioning
confidence: 52%
“…miRNAs promote mRNA degradation by inhibiting translation upon binding to the 3'-untranslated region (3'-UTR) of their target mRNA (12). Complementary binding of an miRNA and mRNA is not exclusive; a single miRNA can target hundreds of mRNAs, which was demonstrated in the present study and a single mRNA can be affected by multiple miRNAs (13)(14)(15)(16)(17). Consequently, miRNAs can act as tumor suppressors or possibly oncogenes depending on the target mRNAs (18,19).…”
Section: Introductionmentioning
confidence: 52%
“…ii) If other signaling pathways or transcription factors, including NF-κB and AP-1 were associated the biological effect of miR-126, further studies are required to investigate their underlying mechanisms and cascade reactions. iii) Although certain targets of miR-126 were reported in different cell types and disease models, including EGFL7 (29), pik3r2 (30), ROCK1 (31), IRS-1 and GOLPH3 (32), to the best of our knowledge, Spred1 was reported as a direct target of miR-126 and was associated with MC activation (11). The present study focused on the direct effect of miR-126 on MC degranulation and its preliminary molecular mechanisms.…”
Section: +mentioning
confidence: 86%
“…A previous study reported that miR-126 was able to regulate PTPN9 in the hematopoietic differentiation of human embryonic stem cells at the post-transcriptional level (29). Frequently described as a tumor suppressor in a number of studies, miR-126 was observed to be downregulated in ESCC tissues and cell lines (32,37–39). However, the interaction between miR-126 and PTPN9 in the process of ESCC remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (32). Rabbit anti-human PTPN9 antibody (dilution, 1:50; cat.…”
Section: Methodsmentioning
confidence: 99%